2021
DOI: 10.3168/jds.2020-19427
|View full text |Cite
|
Sign up to set email alerts
|

Screening of specific nucleic acid targets for Cronobacter sakazakii and visual detection by loop-mediated isothermal amplification and lateral flow dipstick method in powdered infant formula

Abstract: Due to the lack of specific genes for rapid detection methods of Cronobacter sakazakii in food samples, whole genome sequence analysis was performed in this investigation using the basic local alignment search tool. Forty-two DNA fragments unique to C. sakazakii were mined, then primers were designed and screened by PCR and loop-mediated isothermal amplification (LAMP). Two primer sets, CS1 and CS31, were found as specific and stable primers, with their corresponding nucleic acid targets the CSK29544_00235 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In recent years, the amplification of bacterial-specific DNA fragments by PCR technique can accurately identify the presence of bacteria, which is characterized by easy operation, short detection cycle, high sensitivity and specificity [ 19 ]. Therefore, PCR technology used to identify bacteria will likely replace the traditional sputum culture technique in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the amplification of bacterial-specific DNA fragments by PCR technique can accurately identify the presence of bacteria, which is characterized by easy operation, short detection cycle, high sensitivity and specificity [ 19 ]. Therefore, PCR technology used to identify bacteria will likely replace the traditional sputum culture technique in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Different sensitivities of the LAMP technique have been reported in the detection of foodborne pathogens. For example, Fu et al (12) reported an LOD value of 4.50 CFU/ mL targeting specific nucleic acid targets of C. sakazakii in powdered infant formula samples by LAMP. LOD values of 20 and 10 CFU per reaction targeting ompW (28) and ctxA (10) genes of V. cholerae have also been reported by LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the Cronobacter spp. has been divided into seven species and three subspecies [1,2]. Among them, C. sakazakii and C. malonaticus are the main pathogenic bacteria in clinic [3].…”
Section: Introductionmentioning
confidence: 99%